Field performance, alkaloid quantities, and transcriptome profiles of nearly isogenic tobacco lines possessing alternative allelic combinations at the Nic1, Nic2, and Myc2a loci - Rui Shi; Zachary Allen; Tyler Steede; Ramsey S. Lewis (BMC Genomics)
Abstract Tobacco with modified genetics controlling alkaloid accumulation has been of interest because of the possibility of mandated lowering of nicotine levels in combustible cigarettes by regulatory authorities. Transcription factors coded by the Nic1, Nic2, and Myc2a loci act as positive regulators of genes directly involved in alkaloid accumulation. In this research, different combinations of alternative alleles at these loci were assembled in homozygous nearly isogenic lines (NILs). Recessive nic1/nic2 alleles were found to have greater influence on alkaloid reduction as compared to a mutant myc2a allele. When combined into single genotypes, these alleles operated in an additive manner to further reduce alkaloid levels in field and greenhouse experiments. This was at the expense of reduced cured leaf quality, however. An RNA-seq experiment was carried out to investigate global changes in root expression due to different genotypes at these three loci. Up to 1,028 differentially expressed genes (DEGs) were identified between the studied NILs, with expression of most DEGs being downregulated by recessive alleles. In general, the mutant myc2a allele appeared to suppress a subset of previously characterized alkaloid biosynthetic genes with relatively weaker effect as compared to the nic1/nic2 alleles. There was little evidence that root expression of Nic1 or Nic2 genes was affected by allelic variability at the Myc2a locus, or vice versa. The list of DEGs influenced by genotypes at these three loci may contain candidate genes coding for currently uncharacterized enzymes involved with tobacco alkaloid accumulation.